IMPLEMENTASI MARKETING MIX DALAM KEGIATAN PEMASARAN KAIN TENUN PADA GALERI TENUN DESA SETANGGOR LOMBOK TENGAH - Dewi Rispawati (Juremi: Jurnal Riset Ekonomi, 2024)
This research is entitled "Implementation of Marketing Mix in Marketing Activities of Woven Fabrics at the Woven Gallery of Setanggor Village, Central Lombok", which aims to determine the implementation of the appropriate Marketing Mix used in marketing activities of Woven Fabrics at the Woven Gallery of Setanggor Village, Central Lombok. The benefits of this research are as input and consideration for the Woven Gallery of Setanggor Village, Central Lombok in implementing the marketing mix in marketing activities of Woven Fabrics at the Woven Gallery of Setanggor Village, Central Lombok. The type of research in this study is descriptive research, with data collection techniques, namely observation, interview and documentation methods. This research uses data validity checking techniques based on triangulation techniques, by re-checking data that has been obtained through several sources. The types of data in this study are qualitative data and quantitative data and the data sources in this research are primary data and secondary data. Based on the results of the analysis, it is known that the marketing mix that can be applied in marketing activities of Woven Fabrics at the Woven Gallery of Setanggor Village, Central Lombok include: Product, Price, Promotion and Distribution (Place). Implementation of marketing mix at the Setanggor Village Weaving Gallery, Central Lombok so that the woven fabrics sold can be more varied, developed, and well-known, and in demand by consumers, especially on the island of Lombok, not only in Indonesia but also abroad